Waitress - Roiff, Michael; Shelly, Adrienne, 1966-2006.; Russell, Keri, 1976-; Fillion, Nathan, 1971-; Hines, Cheryl; Sisto, Jeremy, 1974-; Griffith, Andy, 1926-2012.; Jemison, Eddie; Temple, Lew.; Night & Day Pictures; Twentieth Century Fox Home Entertainment, Inc. (Beverly Hills, Calif. : 20th Century Fox Home Entertainment, 2007)
Jenna is unhappily married. She squirrels away money and is hoping to win a pie-baking contest so, with the prize money, she'll have enough cash to leave her husband Earl. She finds herself pregnant and her plans are thrown awry. She bakes phenomenal pies at Joe's diner, listens to old Joe's wisdom, tolerates her sour boss Cal, is friends with her fellow waitresses, Dawn and Becky. She, also, finds a mutual attraction with the new doctor in town. Life with Earl becomes less tolerable as her pregnancy advances. Her way out of the marriage is less clear and her affair with the doctor is complicated by his marriage.
DVD, region 1, full screen (1.85:1) presentation; Dolby Digital 5.1 surround.
English or dubbed Spanish dialogue, English, French or Spanish subtitles; closed-captioned.
Keri Russell, Nathan Fillion, Cheryl Hines, Jeremy Sisto, Andy Griffith, Adrienne Shelly, Eddie Jemison, Lew Temple.
Director of photography, Matthew Irving ; editor, Annette Davey ; music, Andrew Hollander ; costume designer, Ariyela Wald-Cohain ; production designer, Ramsey Avery.
MPAA rating: PG-13; for sexual content, language and thematic elements.
Special features: Commentary by producer Michael Roiff and actor Keri Russell; "This is how we made Waitress pie" featurette; "Written and directed by Adrienne Shelly: a memorial" featurette; "Hi! I'm Keri, I'll be your waitress; "The pies have it!" featurette; Fox Movie Channel presents "In character with: Keri Russell" and "In character with: Cheryl Hines" featurettes; a message from Keri Russel about the Adrienne Shelly Foundation; trailers.
Keywords: Waitresses -- United States -- Drama; Pregnant women -- United States -- Drama; Pies -- Drama; Married people -- United States -- Drama; Adultery -- United States -- Drama; Servicio de alimentos -- Estados Unidos -- Teatro; Embarazo -- Estados Unidos -- Teatro; Waiters and Waitresses -- United States -- Drama; Pregnant women -- United States -- Drama; Pies -- Drama; Married people -- United States -- Drama; Adultery -- United States -- Drama; Adultery; Married people; Pies; Pregnant women; Waitresses; United States; Feature films; Comedy films; Feature films; Fiction films; Romantic comedy films; Video recordings for the hearing impaired; Romance -- Feature; Comedy -- Feature; Women -- Feature; Drama; Feature films; Fiction films; Romantic comedy films; Video recordings for the hearing impaired